Hubungan Persepsi Penyakit dan Manajemen Koping dengan Depresi pada Pasien Diabetes Mellitus - Anggraini, Devi; Astuti, Ani; Octavia, Dian (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2022)
DM is a chronic disease that can lead to hopelessness so that it can lead to depression. Several factors are also associated with the incidence of depression in people with diabetes mellitus, namely the perception of the disease and coping management. This study aims to determine the relationship between disease perception and coping management with depression in clients with diabetes mellitus. This research is a quantitative research with a cross sectional research design. The population in this study were all diabetes mellitus clients who visited the Putri Ayu Public Health Center, Jambi City in 2020, amounting to 1,810 people and sampling was done using accidental sampling technique as many as 95 people. The instrument used a questionnaire and the analysis used univariate and bivariate with chi-square test. The results of the univariate analysis showed that there were 66 (69.5%) respondents who had a perception of the disease in the positive category, there were 69 (72.6%) respondents who had coping management in the adaptive category and there were 54 (56.8%) respondents who did not experience depression at diabetes mellitus client. The results of the bivariate analysis showed that there was a relationship between disease perception (p=0.00) and coping management (p=0.00) with depression in diabetes mellitus clients at Putri Ayu Health Center Jambi City in 2021. It is hoped that the Puskesmas, especially nurses, will hold a program health services to provide counseling for patients with diabetes mellitus who experience depression that with continuous examinations it is possible for patients with diabetes mellitus to recover Abstrak Diabetes Mellitus (DM) merupakan penyakit kronis yang dapat menimbulkan keputusasaan sehingga dapat menimbulkan terjadinya depresi. Beberapa faktor juga dikaitkan dengan kejadian depresi pada penderita diabetes mellitus yaitu persepsi penyakit dan manajemen koping. Penelitian ini bertujuan untuk mengetahui hubungan persepsi penyakit dan manajemen koping dengan depresi pada klien diabetes mellitus. Penelitian ini merupakan penelitian kuantitatif dengan desain penelitian cross sectional. Populasi dalam penelitian ini adalah seluruh klien diabetes mellitus yang berkunjung ke Puskesmas Putri Ayu Kota Jambi Tahun 2020 yang berjumlah 1.810 orang dan pengambilan sampel dilakukan dengan menggunakan teknik accidental sampling sebanyak 95 orang. Instrument menggunakan kuisioner Epidemiologic Studies Depression ScaleÂ (CES-D), BPIQ (Brief Perception of Illness Questionaire) dan Jalowiec Coping Scale. Analisa penelitian menggunakan univariat dan bivariat dengan uji chi-square. Hasil penelitian menunjukkan bahwa ada hubungan antara persepsi penyakit (p=0,00) dan manajemen koping (p=0,00) dengan depresi pada klien diabetes mellitus di Puskesmas Putri Ayu Kota Jambi Tahun 2021. Diharapkan pihak Puskesmas khususnya perawat untuk mengadakan program kesehatan untuk memberikan konselingÂ bagi pasien diabetus mellitus yang mengalami depresi bahwa dengan adanya pemeriksaan terus dilakukan memungkinkan pasien diabetes mellitus dapat sembuh. Kata kunci : Persepsi Penyakit, Manajemen Koping, Depresi, DM